EVALUATION OF THE ADDED EFFECT OF SHUNTYADI KWATHA IN THE MANAGEMENT OF AMAVATA VIS A VIS RHEUMATOID ARTHRITIS - Goyal Gaurav*; Rajashekhar C.V (AYUSHDHARA, 2018)
Amavata is a very painful condition due to Vata prakopa avastha, and when Vata is accompanied with Ama then severity of pain increases more. Vitiated Vayu circulates the Ama all over the body through Dhamanies, takes shelter in the Shleshma Sthana (Amashaya, Sandhi, etc.), producing symptoms such as stiffness, swelling, and tenderness in small and big joints, making a person lame. The symptoms of Amavata are identical to rheumatism, which include rheumatoid arthritis and rheumatic fever. Shunthi is a very common household drug, almost everyone have used ginger in so many things as in tea or in curry etc. In all living beings pain is one of the nature’s earliest sign of morbidity. first and foremost duty of a physician is to help a patient to get rid of pain. The conventional science tries to find a cure for this through analgesics, steroidal therapy, etc. which often results in ill effects. Here comes the importance of herbal remedies of Ayurveda. Shuntyadi kwatha show a wide range of therapeutic usages. Because of its properties like Ushanta, Tikshanta, Katu, Tikta rasa, Katu vipaka help in Samprapti vighatana of Aamavata. when Shuntyadi kwatha is used with Simhanada guggulu then, its result increases many fold in Amavata. In this study 40 patients of Amavata were registered and 03 patient (6.66%) were got no improvement, 15 patients got mild -improvement, 22 patient (10%) were got moderate improvement, 0 patient got Marked improvement and complete cure.